Institutional memory and organizational memory: Faces of the same coin - Dos Santos, Juliana Cardoso; Valentim, Marta Lígia Pomim [UNESP] (FapUNIFESP (SciELO), 2021)
Memory has the characteristic of being ubiquitous and is considered a phenomenon of identification and belonging in which the individual is both subject and object. In this context, the objective is to present some differences between institutional memory and organizational memory in order to show that both are integrated, with no subordination. With regard to methodological procedures, this research is qualitative, typologically descriptive and exploratory. For that, a Systematic Literature Review protocol was carried out, covering the period from 2009 to 2019. It is considered that the findings can contribute to enrich the theoretical framework of the scientific field of Information Science, more specifically with regard to institutional memory related to legitimacy and organizational memory linked to the efficiency and effectiveness of organizations. As a result, it is evident that there are no subordinations, but some particularities and individualities between institutional memory and organizational memory, demonstrating that institutional memory is related to the social value of the group, has difficulty in being practical, realistic and objective, it is in the whole instituted, it is not pragmatic, it is an intentional object and a collective phenomenon that deals with power relations; organizational memory, on the other hand, is practical, pragmatic, objective, at the service, focused on concrete actions and on the construction of management processes, and is focused on productivity. As similarities, it was identified that both memory processes are cyclical, mutable, are under constant construction, are unique and should be considered social phenomena, as they are products of social relations. It is considered that the findings can contribute to enrich the theoretical framework of the scientific field of Information Science, more specifically with regard to institutional memory, related to legitimacy, and organizational memory, linked to the efficiency and effectiveness of organizations.
Memória institucional e memória organizacional: Faces de uma mesma moeda
Keywords: Institutional memory; Interrelationships; Memory; Organizational memory